Analysis Of Clean Water Production Capacity Regional Drinking Water Company City Tidore Islands - Tamrin Husaen (Jurnal Ilmiah Wahana Pendidikan, 2023)
The need for clean water is an unlimited and sustainable need, while the need for clean water supply and services is increasing from time to time which is sometimes not matched by service capabilities. This is a challenge that must be faced by the local government and a solution is immediately sought so that the majority of people who depend on PDAMs in the city of Tidore Islands do not lack clean water. The purpose of this study was to determine the prediction of the clean water needs of the population of the city of Tidore Islands in the next 20 years, starting from 2016 to 2036. This research was carried out in the service area of ​​the PDAM, Tidore Islands district, especially on Tidore Island. Prediction of population growth and increasing facilities Social activities are carried out using Arithmetic and Geometric methods. The results of this study indicate that the need for clean water for the people of the city of Tidore Islands in 2036 is for normal use of 488.20 liters/second, for maximum day use is 572.90 liters/second. for use at peak hours of 871.8 liters / second.